Subtype-specific plasticity of inhibitory circuits in motor cortex during motor learning - Chen, Simon X; Kim, An Na; Peters, Andrew J; Komiyama, Takaki (Nature neuroscience, 2015)
This study identifies opposite changes in two main subtypes of inhibitory neurons in the mouse motor cortex during motor learning. With learning, the number of synapses made by somatostatin-expressing inhibitory neurons (SOM-IN) onto the distal dendritic branches of pyramidal neurons decreased, whereas the number of perisomatic contacts made by parvalbumin-positive cells increased. The authors also found that optogenetic disruption of SOM-IN activity resulted in impairment of learning-related dendritic spine reorganization and motor learning. Motor skill learning induces long-lasting reorganization of dendritic spines, principal sites of excitatory synapses, in the motor cortex. However, mechanisms that regulate these excitatory synaptic changes remain poorly understood. Here, using in vivo two-photon imaging in awake mice, we found that learning-induced spine reorganization of layer (L) 2/3 excitatory neurons occurs in the distal branches of their apical dendrites in L1 but not in the perisomatic dendrites. This compartment-specific spine reorganization coincided with subtype-specific plasticity of local inhibitory circuits. Somatostatin-expressing inhibitory neurons (SOM-INs), which mainly inhibit distal dendrites of excitatory neurons, showed a decrease in axonal boutons immediately after the training began, whereas parvalbumin-expressing inhibitory neurons (PV-INs), which mainly inhibit perisomatic regions of excitatory neurons, exhibited a gradual increase in axonal boutons during training. Optogenetic enhancement and suppression of SOM-IN activity during training destabilized and hyperstabilized spines, respectively, and both manipulations impaired the learning of stereotyped movements. Our results identify SOM inhibition of distal dendrites as a key regulator of learning-related changes in excitatory synapses and the acquisition of motor skills.